Development of General Physical Qualities of Girls Football Players in Higher Education Institution - Ziyaev Abdurakhmon Abdullaevich (European Science Publishing, 2023)
Today the number of young people playing football is growing day by day. Undoubtedly, this is a sign of the correctness of the reforms being carried out in our country. Finding athletes who are currently talented among our young players is one of the urgent tasks of today in order to focus on long-term training. We know that physical exercise has a positive effect on the nervous and various systems of the body, elevates the soul, strengthening human health. Therefore, one of the main aspects is to develop the stamina of players to achieve good results in a sport like football.
Keywords: Football, human health, physical exercise, sports activity, personal characteristics, level of requirements.